A Malaysian Non-Governmental Organizations (NGO) Experience in Organizing the Maternal and Child Health (MCH) Outreach Clinics for Malaysia’s Interior Indigenous Tribes - A Y, Yahaya; F M, Aina; M Z, Nurul Huda (International Journal of Human and Health Sciences (IJHHS), 2025)
Malaysia’s interior indigenous tribes, residing in remote areas of the tropical rainforest, face significant health disparities. This paper examines the role of medical non-governmental organization (NGO) such as Islamic Medical Association of Malaysia Response and Relief Team (IMARET) in aiding the Ministry of Health mobile teams to enhance the reach and frequency of maternal and child health (MCH) services. From 2015 to 2023, IMARET conducted 60 missions to remote indigenous communities, providing medical services to 10,832 patients. Starting in 2021, IMARET included antenatal and child immunization services as part of its outreach efforts, attending to 170 pregnant ladies and vaccinating 246 children. This expansion reflects IMARET’s commitment to addressing the specific needs of expectant mothers and children in these underserved communities. This paper also explores the challenges encountered, including maintaining proper records, lack of proper facility, cold chain management, demographic of the villages, off-road terrain conditions, adverse weather conditions, availability of knowledgeable volunteer doctors, communication barriers with villagers, and funding constraints. Effective collaboration between IMARET and government agencies is critical for improving maternal and child health outcomes in these communities. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S36